Um protótipo do paraíso à brasileira: convergências e divergências entre o Solo Sagrado de Guarapiranga da Igreja Messiânica Mundial do Brasil e os Solos Sagrados originais da Igreja Messiânica Mundial, no Japão - Ribeiro, Carlos Roberto Sendas (2009)
The present thesis focus the Guarapiranga Sacred Grounds, built in the city of São Paulo by the Church of World Messianity of Brazil. It intends to find the convergences and divergences with the originals Sacred Grounds built by the mother-church Church of World Messianity, in Japan, which inspired the Brazilian one. The Sacred Grounds, as paradise models, play a fundamental role in the Church of World Messianity religious work. They are the physical expression of the ideal of its founder, Mokichi Okada (1882-1955), who stated that, through revelation, he had received the mission of starting the establishment of paradise on Earth, the Ideal World, consolidated in the Truth, Virtue and Beauty trilogy, into which the current civilization will be transformed in this 21st century. For this purpose, Okada built three paradise prototypes at Hakone, Atami and Kyoto cities, in Japan, to inspire the establishment of similar prototypes in others countries, until the whole world becomes a paradise. Therefore, aware of the several different aspects, not only of the geographic and cultural issues between Japan and Brazil but also of the specific characteristics of the Church of World Messianity from each country, we seek to answer the question: What and which adaptations were necessary to the transplantation process of a Sacred Ground from Japan to Brazil? What kind of adaptations in the project as well as in the functioning of the Brazilian paradise prototype were necessary due to the different geographic conditions, such as climate, vegetation and landscape, beyond different cultural, religious and social origins, with their respective habits? The theoretical fundamental chosen to do the analysis was Martin Bauman s model of Religious Transplanting Theory. The research allowed us to conclude that the convergences and the divergences that took place in the transplantation process of the Sacred Grounds built in Japan to Brazil, besides making easier the reading, by the Brazilian community, of the main topics of the doctrine that encouraged its construction, added innovative shapes to the architectural and landscaping models of the original paradise prototypes, which in their turn, can inspire the Messianity members from other countries to build their own prototypes